2020
DOI: 10.1007/s13592-020-00817-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of commercial queen rearing methods on queen fecundity and genome methylation

Abstract: The queen and worker castes of the honey bee are very distinct phenotypes that result from different epigenomically regulated developmental programs. In commercial queen rearing, it is common to produce queens by transplanting worker larvae to queen cells to be raised as queens. Here, we examined the consequences of this practice for queen ovary development and genome-wide methylation. Queens reared from transplanted older worker larvae weighed less and had fewer ovarioles than queens reared from transplanted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…(2021); Yi et al (2021) and Yagound et al (2020). We find around 1,500 genes per sample show allele-specific DNA methylation with slightly lower numbers in worker thorax tissue (Fig.…”
Section: Consistency Of Parent-of-origin Dna Methylation In the Honeybeementioning
confidence: 74%
See 2 more Smart Citations
“…(2021); Yi et al (2021) and Yagound et al (2020). We find around 1,500 genes per sample show allele-specific DNA methylation with slightly lower numbers in worker thorax tissue (Fig.…”
Section: Consistency Of Parent-of-origin Dna Methylation In the Honeybeementioning
confidence: 74%
“…We then called allele-specific DNA methylation in independently generated honeybee female data sets (n = 33) spanning various tissues of both workers and queens from Cardoso-Júnior et al . (2021); Yi et al . (2021) and Yagound et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the queen cells with egg and larvae were kept in the same colony, and newly emerged queens were harvested immediately for weight. Some of emerged queens were kept in queen-less colonies for the number of ovarioles, the scoring ovariole number method was the same as previous report (Yi et al,2020), and 4 newly emerged queens in each group were kept in mating colonies and mated naturally. The rest of emerged queens were snap-frozen in liquid N 2 for queen thorax size measurement (queen thorax length, width, weight).…”
Section: Insects and Queen Rearingmentioning
confidence: 99%
“…In addition, worker bees will reform worker cell with egg or larva into queen cell and the egg or larva will develop to a new queen when the colony loss the old queen bee unexpectedly. Studies revealed that the quality of queens reared by young larvae were less favored than queens reared by eggs, and the quality of queens decreased with the reared larvae age (Woyle.,1971;Rangel.,2012;Yi et al,2020). Also, the growth of colonies with queens reared with older larvae is slower than that reared with younger larvae (Rangel.,2012).…”
Section: Introductionmentioning
confidence: 99%